Telaah Perubahan Stratifikasi Sosial Masyarakat Banten Sebelum Pemberontakan Tahun 1888 - Kristoforus Bagas Romualdi (Universitas Veteran Bangun Nusantara, 2023)
This study aims to examine changes in social stratification in Banten society before the 1888 peasant revolt in the area. The research approach used was qualitative with historical methods. The sources used in this historical method are document sources in the form of books and relevant research articles. The results of the study show that social stratification in Banten before the revolt in 1888 was divided into traditional stratification and changed to colonial. The difference between the two stratifications lies in the position, function, influence, rights, and obligations of groups occupying the upper, middle and lower layers. The stratification of the colonial period which tended to be oppressive became the cause of the emergence of upheavals until the revolt of Banten Peasant’s in 1888.